REPRESENTASI CANCEL CULTURE DI KOREA SELATAN DALAM FILM PILOT (2024) - Adani, Sharfina Rahmanita; Burhan, Amelia (Multikultura, 2025)
Cancel culture is a social phenomenon that occurs when an individual receives public backlash due to actions or statements considered to violate social norms. This phenomenon has become increasingly prominent in South Korea, attracting attention in its highly collective and responsive digital society, which has led to its portrayal in various media works. One such work is the film Pilot (2024), which tells the story of a famous pilot's reputation falling after a gender-biased comment of his spread widely online and drew public scrutiny. This study aims to analyze the representation of cancel culture in the film Pilot (2024) using a qualitative approach with the Critical Discourse Analysis (CDA) method developed by Jäger and Maier. The analysis reveals that the film represents cancel culture as a complex social mechanism through discourse construction reflected in language, actions, and visual elements. This representation illustrates how power dynamics, gender bias, and expectations of professionalism interact to shape social consequences for individuals deemed to have committed a transgression. The film also portrays various responses to social pressure and highlights the role of social media as a primary space for shaping public opinion in the digital era.